Salivary oxytocin mediates the association between emotional maltreatment and responses to emotional infant faces. - Bhandari, R; Bakermans-Kranenburg, M; van der Veen, R; Parsons, C; Young, K; Grewen, K; Stein, A; Kringelbach, M; van IJzendoorn, M (2014)
Childhood emotional maltreatment has been associated with a higher risk for maltreating one's own offspring. In the current study, we explored a possible role of oxytocin in mediating the association between childhood emotional maltreatment and participants' interpretation of infant facial expressions. Oxytocin levels were measured in 102 female participants using saliva samples. They rated the mood of thirteen infants with happy, sad and neutral facial expressions. Emotional maltreatment indirectly influenced responses to happy infant faces by modulating oxytocin levels: higher self-reported emotional maltreatment was related to higher levels of salivary oxytocin which were in turn related to a more positive evaluation of happy infant expressions, but not to the evaluation of sad infant expressions. Oxytocin receptor polymorphism rs53576 did not moderate the relation between maltreatment experiences and salivary oxytocin levels. Early emotional maltreatment might indirectly affect emotional information processing by altering the oxytonergic system.